STAKEHOLDERS’ INSIGHTS INTO CHILD AND ADOLESCENT TO PARENT VIOLENCE AND ABUSE (CAPVA): A METASYNTHESIS OF QUALITATIVE RESEARCH - Prota, Marial; Cohen, Keren (International Journal of Child, Youth and Family Studies, 2025)
Child and adolescent to parent violence and abuse (CAPVA) is one of the more complex areas within the domestic abuse domain. There is no clear consensus about the definition of CAPVA, nor are there widely accepted policies and guidelines about how to approach it. By reanalyzing findings collected from 21 qualitative studies that included children, adolescents, and parents who have experienced CAPVA and professionals who supported them, the current metasynthesis aims to contribute to the growing body of research in the area and to move towards developing more coherent policies and professional guidelines. Current findings highlight how the cycle of CAPVA impacts and is impacted by inherent terminological contradictions, relational tensions between parents and their children, the perceived attribution of its causes, and the accessibility of support systems. The multiple interconnected factors that were found lead to a comprehensive psychosocial model of CAPVA with practical implications for related services.